Qualificar é preciso? Um estudo sobre a política de qualificação profissional em unidades sucroalcooleiras do Triângulo Mineiro/Alto Paranaíba-MG - Marques, Rejane Siqueira Silva (2012)
The title of this research is intended to be provocative enough in a scenario where the qualification is seen as the "touchstone" and with which workers, as to possess, compete advantageously in the market. In the case of this sector, much is present the argument that there is not enough skilled labor force that can corroborate the productive restructuring of the agricultural sector, especially by providing the necessary conditions for the implementation of mechanized harvesting and consequent reduction of activity manual cutting cane sugar, seen as a precarious job. Part of the resolution of this issue would be on the qualification of cane cutters and reintegration of those in the productive sphere. Understanding professional qualification as a set of knowledge, skills and abilities required to perform a particular work process, so that the need of capital to expand the profit rate is met, a study was conducted on a group of companies located in the region of sugarcane Triangulo Mineiro/Alto Paranaiba- MG, with the goal of understanding the implementation process of professional qualification programs targeted to sugarcane workers. Research shows that over 80% of the sugarcane farm workers - especially those with low education and migrate constantly - has not been contemplated by the professional training program developed by the group. The program was targeted at young workers and urban experiences of work, making the qualification they went through, only a certification of skills they already possessed. In this sense, the discourse on the qualification of the cane cutters is presented more as an industry rhetoric than action to minimize unemployment generated by mechanization.